2016
DOI: 10.4067/s0718-95162016005000054
|View full text |Cite
|
Sign up to set email alerts
|

Dairy slurry application to grasslands and groundwater quality in a volcanic soil

Abstract: Research in volcanic-ash soils has shown that they largely capture the dairy slurry following application to land; however, their hydrological properties would favor nutrient leaching. Our objective was to evaluate the contribution of biogeochemical and hydrological controls on the pollution of groundwater by cattle slurry applied to a permanent grassland growing on a volcanic soil. We sampled groundwater chemistry since 10 months before the fertilization (three samplings), and 16 months after, with samplings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Soil retention was calculated as the difference in the soil pool between control and fertilized plots. Other sources were Staelens et al (2003) and Huertas et al (2016)…”
Section: Soil Chemical Analyses and Mass Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Soil retention was calculated as the difference in the soil pool between control and fertilized plots. Other sources were Staelens et al (2003) and Huertas et al (2016)…”
Section: Soil Chemical Analyses and Mass Balancementioning
confidence: 99%
“…They attributed their findings to the high salt content of the raw effluents, as well as the flooding conditions that the trees were exposed to. Conversely, nationally, the evidence that native vegetation can fulfill a filter effect is only recently emerging (Cuevas et al 2014;Little et al 2015;Huertas et al 2016). These studies suggest an important role of soils and native vegetation in the control of diffuse pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the floodplain groundwater showed no diurnal signal, probably because water is not a limiting resource in this environment, as tree roots are extensively submerged. Furthermore, during the course of slug tests Huertas et al (2016) observed a very fast recovery of the floodplainʼs water table, in the order of minutes, compared to slope wells (30 min) and upland wells (more than 1 h). The slope's groundwater could be difficult to relate to the local Et because its diurnal fluctuations were also very out-oftime with respect to common Et-cycles.…”
Section: Evapotranspirationmentioning
confidence: 99%
“…This pattern also discards recent causes used to explain the present DSS, such as water viscosity fluctuations (Schwab et al, 2016). The DSS has also been found to begin when monthly Et 0 surpasses monthly rain in November and ends when this pattern reverses (April; Huertas et al, 2016). Meteorological variables such as air temperature, solar radiation, and Et 0 are well known to progressively increase from winter to summer (Cruz and Calderón, 2008;Sánchez, 2016).…”
Section: Stream and Meteorological Variablesmentioning
confidence: 99%